PTSD in parents of children with severe diseases: a systematic review to face Covid-19 impact - Martina Corsi; Alessandro Orsini; Virginia Pedrinelli; Andrea Santangelo; Carlo Antonio Bertelloni; Niccolò Carli; Rodolfo Buselli; Diego Peroni; Pasquale Striano; Liliana Dell'Osso; Claudia Carmassi (BMC, 2021)
Abstract Context The literature agrees on the impact of post-traumatic stress symptoms in parents of seriously ill children but there is less clarity about the real extent and gender differences of this psychopathological risk. The recent Covid-19 outbreak highlighted new burdens for researchers on Post Traumatic Stress Disorder (PTSD) and clear evidence-based knowledge on this issue is timely needed. Objective In this review, we present a synthesis of the updated evidence on PTSD rates in parents of children with severe diseases. We also aim to try to understand if research in this field has been refined over time with the long-term intent to better face the new challenges of Covid-19 in the paediatric field. Data sources The PubMed database was searched. Study selection Studies were included if they assessed PTSD in parents of children diagnosed with physical illnesses. Data extraction Of 240 studies, 4 were included. Results Analysis of the 4 studies revealed 2 studies with PTSD rates around 20% and in line with previous best-evidence. All 4 studies tried to provide more data on fathers, however, all the studies present the lack of a control group. Limitations The limited number of studies, which also differ widely in the methodology used. Conclusions Methodological errors evidenced in all the 4 studies limit their reliability, making the understanding of the paediatric caregiver's concern regarding PTSD still difficult. More sound research is needed.